Ketidaktaatan Sipil dan Pilihan Golput : Sebuah Tinjauan Injili - Togardo Siburian (Asosiasi Teolog Indonesia, 2015)
This article seeks to connect the ethics of civil disobedience with the practices of golput (abstaining from voting), that is, purposeful abstention from voting in Indonesia's general elections. By describing golput as a form of civil disobedience—for its ability to mobilize on principle; for its aims to achieve certain moral ideals—I argue that golput comprises the conscientious and soft-resistance of many citizens, in their struggle for civil rights. Evangelicals and their churches ought to perceive this issue of social ethics primarily within the framework of theology, not politics. Indeed during Indonesia's Reformasi era many of democracy's ideals—including justice and prosperity—have been misused for the fulfillment of the self-interest of the few people in power. Indonesian Christians, therefore, have a responsibility to act against such abuses of power, necessitating a theological framing for understanding the praxis of golput as a form of civil disobedience.